2013
DOI: 10.2174/138945013804806479
|View full text |Cite
|
Sign up to set email alerts
|

A Key Role for Connexin Hemichannels in Spreading Ischemic Brain Injury

Abstract: Brain damage resulting from cerebral ischemia remains a significant problem at all stages of life. In adults, ischemic stroke is the third leading cause of death and the leading cause of disability in the developed world. In term newborns, moderate to severe brain damage after hypoxia-ischemia (HI) occurs in 1-3 per 1000 live births. One of the most striking features of HI injury is that after initial recovery of cellular oxidative metabolism, there is a delayed, 'secondary' mitochondrial failure that spreads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 127 publications
(191 reference statements)
0
40
0
Order By: Relevance
“…Among them, GJA1, SLCA2 and Leukocyte surface antigen CD47 (CD47) showed decreased, while APOE, MAP2K1, TF and PEA-15 showed increased expression in CCH rats. Interestingly, downregulation or absence of GJA1 reduced neuronal loss, capillary fragmentation, astrocytosis and microglia activation (Davidson et al, 2013), while reactive astrogliosis increases GJA1 expression (Masaki et al, 2013, Wallach et al, 2014. Moreover, brain microgliosis and astrogliosis are also affected in APOE transgenic mice (Bales et al, 1999) and the absence of APOE dramatically reduced amyloid deposition and the resulting astrogliosis and microgliosis (Ophir et al, 2003).…”
Section: Chronic Cerebral Hypoperfusion Inflammatory Effectsmentioning
confidence: 99%
“…Among them, GJA1, SLCA2 and Leukocyte surface antigen CD47 (CD47) showed decreased, while APOE, MAP2K1, TF and PEA-15 showed increased expression in CCH rats. Interestingly, downregulation or absence of GJA1 reduced neuronal loss, capillary fragmentation, astrocytosis and microglia activation (Davidson et al, 2013), while reactive astrogliosis increases GJA1 expression (Masaki et al, 2013, Wallach et al, 2014. Moreover, brain microgliosis and astrogliosis are also affected in APOE transgenic mice (Bales et al, 1999) and the absence of APOE dramatically reduced amyloid deposition and the resulting astrogliosis and microgliosis (Ophir et al, 2003).…”
Section: Chronic Cerebral Hypoperfusion Inflammatory Effectsmentioning
confidence: 99%
“…Previous research has revealed that unopposed connexons also play an important role. They mediate the release of paracrine molecules, which in turn transmit cell death messages by the secretion of intracellular mediators (such as ATP, Nicotinamide adenine dinucleotide (NAD + ), and glutamate), which ultimately leads to cell edema [103,104]. …”
Section: Clinical Strategies Of Antioxidants In Hiementioning
confidence: 99%
“…Decreased electrical coupling during acute MI has been correlated with dephosphorylation and reorganization of Cx43, as well as translocation from the cell surface to intracellular pools [60,61]. While the reduction in Cx43 is likely a protective mechanism (GJs are implicated in the spread of injury signals in skin [62], neural tissues [63], and heart [64]), Cx43 lateralization interrupts normal electrical conduction patterns in the heart, and may contribute to arrhythmias [1013]. …”
Section: Changes In the Structure And Function Of The Infarcted Heartmentioning
confidence: 99%